Addressing vulnerability and enhancing resilience in coastal areas: a systematic literature review - Aditantri, Rahmatyas; Zen, Irina Safitri; Ahmad Sarkawi, Azila (IIUM Press, 2025)
Coastal areas are regions that aresusceptible tohazardsdue tothe impact of climate change. In adapting to thevulnerability condition, itisnecessaryto understand theadaptive strategy which can enhance resilience in coastalareas. This study examinesthe integration ofvulnerability and resilience in coastal areasto inform adaptivestrategiesin disaster management. Through a systematicliterature review, the study highlights fourkey gaps:the integration of local knowledge and longitudinal studies, theimpact of socio-economicfactors, aninterdisciplinaryapproach and technology innovation,and community-basedapproaches.